Consumers' perception on quality for edible cooking palm oil in Taman Rasmi Jaya, Ampang Selangor / Siti Nur Atiqah Bux Sheikh Johari Bux - Bux Sheikh Johari Bux, Siti Nur Atiqah (Faculty of Plantation and Agrotechnology, 2016)
Elaeis guineensis commonly known as palm oil tree is one of the major commodities for Malaysia Edible palm oil comes from palm oil is one of the most important components of food and major sources of energy for a human. The research explores the consumer perception of quality for edible cooking palm oil in Taman Rasmi Jaya, Ampang Selangor. The purpose of this study is to determine the factor that influences the trend and quality and measure the awareness in terms of health issues for palm oil among consumer. Nowadays, the current issue about edible cooking palm oil is an abundance demand and health product. The method of study used questionnaire was obtaining 265 respondents. The data analysis using SPSS Version 20.0 and the result represent using factor analysis, cross tab, cross tab chi-square, correlation test. The production of palm oil should be effective when the product was supplied efficiency by taking advantages from the advertisement. The result has shown that consumer purchasing edible cooking palm oil because they used it as the main material in a prepared meal in daily life. However, the consumer is still a lack of knowledge on the benefit of edible palm oil toward their health . This study focuses on consumer choice based on the trend, quality and health factors conducted in Taman Rasmi Jaya, Ampang, Selangor. Some improvements can be made by related agencies such as awareness campaigns about the advantages of edible cooking palm oil for improving the production of edible palm oil.